Assessment of the impact of battery selection on the feasibility of hybrid renewable energy systems. Issue 4 (11th March 2022) - Chaurasia, Ravi; Gairola, Sanjay; Pal, Yash
Abstract: This paper assesses the technical, economic, and environmental feasibility of photovoltaic (PV)/wind turbines (WT)/diesel generator (DG)/battery‐based hybrid renewable energy systems (HRES) using lead acid (LA), lithium‐ion (LI), and iron Edison nickel‐iron (IE) battery technologies (BTs). The energy cost is optimized, and the obtained results are compared to select the best hybrid system. The LI battery employed in the PV/DG/battery system (206.43 kW PV, 50 kW DG, 53.04 kWh LI batteries, and 61.1 kW converter) performed comparatively much better, as levelized cost of energy (LCOE) was reduced by around 28% and 20%, and greenhouse gas (GHG) emissions were reduced by 31% and 6% as compared to the LA and IE batteries employed in HRES, respectively. In addition, sensitivity analysis reveals that the capital cost of PV and the discount rate are more critical to determining the LCOE and renewable penetration. In contrast, the effect of the battery cost and inflation rate is relatively small. Finally, comparing the optimal resource configuration has confirmed that PV/DG/LI has significantly reduced LCOE (58% less than DG/LI) and GHG emissions (87% less than DG/LI). Abstract : Methodology utlized